New topics of constitutional rigidity - Sánchez Morales, Mauricio (Universidad Autónoma de Tamaulipas, 2019)
Constitutionalism has, as a key issue, that the states use the Constitution as the supreme norm of the entire legal order. Its evolution has moved from a liberal model to a democratic one, where being under a rigid constitution plays a role of utmost importance at the moment of trying to reform the content of the Social Pact. It is precisely in this aspect that the existence of different models at the state level is observed where the aggravating factors vary to such a degree that it is feasible to rethink what should be understood by a rigid constitution in contemporary Mexico and what elements should be included in attention to a democratic state like ours.